29.5% of Malaysians aged 16-19 from poor families have mental illness - Amalia, Madihie (New Sarawak Tribune, 2016)
An excerpt statement from a speech by YB Datuk Fatimah at International ProCoun'16 at Hilton on 13th October 2016